Recurrent pregnancy loss, plasminogen activator inhibitor-1 (-675) 4G/5G polymorphism and antiphospholipid antibodies in Czech women - Subrt, Ivan; Ulcova-Gallova, Zdenka; Cerna, Monika; Hejnalova, Marketa; Slovanova, Jitka; Bibkova, Katarina; Micanova, Zdenka (American journal of reproductive immunology (New York, N.Y., 2013)
PROBLEM: This study compares the frequencies of plasminogen activator inhibitor-1 (-675) 4G/5G polymorphism and its relationship with eight antiphospholipid antibodies (aPLs) in serum of 157 patients with repeated pregnancy loss (RPL). METHOD OF STUDY: PAI-1 (-675) 4G/5G polymorphism was determined using standard PCR-RFLP method. Enzyme-linked immunosorbent assay was used for the detection of aPLs against ph-serine, ph-ethanolamine, ph-inositol, ph-DL-glycerol, phosphatidic acid, annexin V, cardiolipin, and beta2-GPI. Allelic frequency and distribution of genotypes were calculated. The prevalence of the risk conferring 4G allele and 4G/4G homozygous genotype in patients and controls was compared, and the correlation between aPLs positivity and PAI-1 4G/4G genotype was tested by chi-square test. RESULTS: Statistically highly significant correlation between RPL and PAI-1 (-675) 4G/4G genotype was found. No correlation between PAI-1 (-675) 4G/5G polymorphism and the presence of antiphospholipid antibodies in RPL patients was observed. CONCLUSIONS: PAI-1 (-675) 4G/4G homozygous genotype increases the risk of RPL independently from the aPLs positivity.
Keywords: běloši; antifosfolipidové protilátky; genotyp; těhotenství; Genotype; Antibodies, Antiphospholipid; Česká republika; Adult; Abortion, Habitual; Czech Republic; polymorfismus genetický; Polymorphism, Genetic; ženské pohlaví; Humans; Pregnancy; habituální potrat; frekvence genu; inhibitor aktivátoru plazminogenu 1; White People; Plasminogen Activator Inhibitor 1; Gene Frequency; dospělí; Female; lidé